Sustainable Urban Future in Southern Europe - What About the Heat Island Effect? - Eleftheria Alexandri; Phil Jones (European Regional Science Association (ERSA), 2006)
In general cities, and especially cities in hot zones, as the Mediterranean, suffer from raised temperatures in the city core, generally known as the heat island effect. Raised temperatures, especially in summer, may turn city centres into unwelcome hot areas, with direct effects on energy consumption for cooling buildings and morbidity and mortality risks for the population. These raised temperatures in the city centre derive from the altered thermal balances in urban spaces, mainly due to the materials and activities taking place in cities, by far different to those in rural areas. The notably raised thermal capacity of urban materials, their low albedo and their lack of porosity are of the main characteristics of urban materials, responsible for the formation of raised urban temperatures. The general lack of vegetation is a strong characteristic of the formation of the heat island effect. If building surfaces, which are greatly responsible for the formation of raised urban temperatures are covered with vegetation (roofs with grasses and walls with ivies), it is expected that urban temperatures could lower significantly. With the case study of the city of Athens, this paper explores quantitatively how raised urban temperatures could reduce in the hot and dry Mediterranean summer, when the building envelope is covered with vegetation. With the use of a prognostic, two-dimensional, micro-scale heat and mass transfer model, the effect of vegetation in urban canyons with different geometries and orientations is explored and how this could be applied at an urban scale. The effect of vegetation on the building envelope is examined on the outdoors thermal comfort and the energy consumption for cooling. Conclusions are drawn about the relationship of the effect of diverse amounts of vegetation with the urban geometry and orientation and whether such a proposal could prove beneficial for cities in the South of Europe.
Keywords: 330